Newness in Old Testament Prophecy: An Intertextual Study - Leene, Henk (Oudtestamentische Studiën, Old Testament Studies, 2013)
In Newness in Old Testament Prophecy: An Intertextual Study Henk Leene examines literary and text-genetic relations between the promises regarding new things in Isaiah, Jeremiah and Ezekiel, paying due attention to the new song heralding Yhwh's kingship in the Psalms.